Development of pmp Gene-Specific PCR Assay with A Host Specific Internal Control for Chlamydophila felis - Cantekin, Zafer; Solmaz, Hasan; Altug, Nuri; Ozmen, Gamze Ozge (The Thai Journal of Veterinary Medicine, 2014)
Chlamydophila felis is the primary bacterial agent of conjunctivitis and upper respiratory disease in cats. Transmission of the disease requires close contact between cats. Polymerase chain reaction is a useful tool for detection of this organism. The aim of this study was to develop a polymerase chain reaction assay with an internal amplification control for the detection of C. felis. Primer pairs were designed specifically for polymorphic membrane protein gene of C. felis and cytochrome b gene of cat, and their specificity and sensitivity were examined. Primers specific for both genes were then multiplexed. In the simplex polymerase chain reaction analyses with 10-fold dilutions, C. felis DNA was detected with designed primers for polymorphic membrane protein genes up to 1.6 pg/µl and cat DNA was demonstrated in all samples in the polymerase chain reaction. Moreover, in the multiplex polymerase chain reaction, C. felis DNA and cat DNA were detected together. These designed primers specific for C. felis might have potential for research on infections and shedding of this organism in cats as the internal control host specific primers might have potential for using internal control for detection of different microorganisms in cats.